Regional Integration and Energy Sustainability in Africa: Exploring the Challenges and Prospects for ECOWAS. (10th December 2019) - Akinyemi, Opeyemi; Efobi, Uchenna; Osabuohien, Evans; Alege, Philip
Abstract: This study explores the extent to which regional integration can be a viable tool in driving energy sustainability in the Economic Community of West African States (ECOWAS) sub‐region of Africa and vice versa. It examines the existing opportunities and the attendant challenges for improved firm productivity in the region through the appraisal of the ECOWAS West African Power Pool. Using three measures of energy sustainability, namely energy security, energy equity and environmental sustainability; the study presents the performance of the ECOWAS sub‐region in ensuring regional integration for energy sustainability. The findings from the study reveal, inter alia, that there are prospects and benefits for energy integration for sustainable development in the region. However, even though some progress had been made, there are many challenges. Also, where progress had been made, it is not uniform across the region, though factors such as rising population and political instability could be responsible. It is recommended that the political economy surrounding regional energy integration should be given a priority among member states to ensure that there is positive political will for speedy achievement of set goals. Also, investment in human capital to manage the different projects and maintain the facilities cannot be overemphasized.